Influence of academic performance, level of play, sports success, and position of play on the motivation of the young football player - Ureña-Lopera, C.; Morente-Oria, H.; Chinchilla-Minguet, J. L.; Castillo-Rodriguez, A. (International Journal of Environmental Research and Public Health, 2020)
Background: Motivation in athletes is a state that fluctuates due to multiple factors that can, in turn, negatively or positively influence sports performance. Objectives: The aim of this study was twofold, being, on the one hand, to analyze the motivation of soccer players of developmental age in two different contexts (training time (baseline) and the precompetitive time) depending on the category, sports success and playing position, and, on the other hand, to find relations of the motivation dimensions with the academic performance and physical characteristics of the soccer players. Methods: One hundred and forty-one under 16 (U16) soccer players were selected (age: 14.7 ± 0.5; height: 170.4 ± 7.2 cm; weight: 61.6 ± 10.0 kg). Data on academic performance, physical and socio-demographic characteristics were recorded, and in two differentiated moments, the motivation dimensions, both in training and in competition. Results: The results showed that the general motivation decreases with the competition, and in particular, the intrinsic motivation, where the precompetitive evaluation is lower than the basal, in both categories (p < 0.05). In addition, demotivation is explained by 10.2%, 19.8%, and 23.9% by fat mass, by academic performance, and by category, respectively; and the extrinsic motivation of external regulation is explained in 26.0% by the academic performance factor (p < 0.01). Conclusions: U16 soccer players show lower levels of motivation at moments prior to the sports competition, and these dimensions of motivation are explained by the category, academic performance, and fat mass.